EPIDEMIOLOGICAL STUDY OF ACQUIRED DEVELOPMENTAL DEFECTS OF ENAMEL IN CHILDREN BETWEEN 3 AND 19 YEARS OLD FROM DOLJ COUNTY, ROMANIA - Mihai Popescu; Veronica Mercuț; Mihaela Ionescu; Stelian Mihai Sever Petrescu; Adela Cenușoiu; Adrian Stănuși; Marilena Bătăiosu (Romanian Society of Oral Rehabilitation, 2020)
Aim of the study The aim of our study was to determine and compare the prevalence and severity of acquired developmental defects of enamel (DDE) in a group of children coming from a rural area in Dolj County, Romania, aged between 3 and 19 years. Material and methods A total of 213 children were examined using the modified DDE Index, for screening studies. Their assessment included the clinical examination, performed by completing an excel document. Results The prevalence of DDE was 11.27%. Of the 5452 primary and permanent teeth examined, 49 (0.90%) had some form of DDE. Diffuse opacity was the most common type of DDE observed in primary teeth, while in permanent dentition, the number of the 2 forms of opacity was very similar. We did not find any hypoplasia. Conclusions DDE is currently increasing, having major implications for children's lives, which makes it a significant public health problem.